2019
DOI: 10.1038/s41388-019-0942-z
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prevents liver tumourigenesis by attenuating fibrosis in a transgenic mouse model of hepatocellular carcinoma

Abstract: Metformin is a hypoglycaemic agent used to treat type 2 diabetes mellitus (DM2) patients, with a broad safety profile. Since previous epidemiological studies had shown that the incidence of hepatocellular carcinoma (HCC) decreased significantly in metformin treated DM2 patients, we hypothesised that intervention with metformin could reduce the risk of neoplastic transformation of hepatocytes. HCC is the most common primary liver malignancy and it generally originates in a background of liver fibrosis and cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 55 publications
0
48
0
3
Order By: Relevance
“…MET (p.o) was administered at 300 mg/kg in drinking water. This can be translated to the human equivalent dose using the Reagan‐Shaw method . By the end of the experiment and after the rats were anesthetized, the trunk blood samples were collected from each rat.…”
Section: Methodsmentioning
confidence: 99%
“…MET (p.o) was administered at 300 mg/kg in drinking water. This can be translated to the human equivalent dose using the Reagan‐Shaw method . By the end of the experiment and after the rats were anesthetized, the trunk blood samples were collected from each rat.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic therapies targeting certain metabolism processes provide alternatives for chemoresistant patients. For example, it has been reported that metformin can prevent liver carcinogenesis (Shankaraiah et al , ) and treatment with metformin is associated with favorable prognosis in patients with HCC (Schulte et al , ). Determining the responders of metabolic therapies has proven to be challenging (Rosario et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes patients treated with metformin have a lower risk for HCC development compared with those taking other antidiabetic drugs in a large populationbased prospective clinical epidemiological survey (1). Besides, metformin alone or combined with other drugs obviously counteracts malignant features of HCC through multiple mechanisms (2)(3)(4)(5), suggesting an obvious antitumor role of metformin in HCC development and progression. Similar to other chemotherapy drugs, metformin may be also developed into drug tolerance and resistance in HCC during long-term treatment.…”
Section: Introductionmentioning
confidence: 99%